Relationship Between Red Blood Cell Distribution Width and All-Cause Mortality in Disseminated Intravascular Coagulation Patients: A Retrospective Analysis - Hu B (Dove Medical Press, 2021)
Bin Hu,1 Jinxia Cao,1 Yangyang Hu,2 Zuoan Qin,3 Jun Wang1 1Department of Hematology, First People’s Hospital of Changde City, Changde, Hunan, People’s Republic of China; 2Department of Rheumatology and Immunology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 3Department of Cardiovascular Medicine, First People’s Hospital of Changde City, Changde, Hunan, People’s Republic of ChinaCorrespondence: Jun WangDepartment of Hematology, First People’s Hospital of Changde City, 818 Renmin Road, Wuling District, Changde, 415000, Hunan, People’s Republic of ChinaTel +86-736-7788720Email xueyeke2020@sina.comPurpose: Studies regarding death risk factors of disseminated intravascular coagulation (DIC) patients were limited. We conducted this study to investigate whether red blood cell distribution width (RDW) was independently related to all-cause mortality of DIC patients.Methods: We used data from the Medical Information Mart for Intensive Care III version 1.4 (MIMIC-III v1.4). A total of 2098 patients with DIC were included. The main outcome was in-hospital all-cause mortality.Results: After adjusting for potential covariates, the in-hospital all-cause mortality was positively correlated with RDW. The hazard ratio (HR), 95% confidence intervals (CI), and P-value were 1.08, (1.05, 1.12), and P< 0.0001, respectively. The Kaplan–Meier curve found DIC patients with elevated RDW had a lower survival rate than patients with normal RDW (P< 0.0001). A nonlinear relationship between RDW and mortality was found with the inflection point 19.2%. When RDW < 19.2%, RDW was positively correlated with in-hospital all-cause mortality of DIC patients (HR (95% CI): 1.17 (1.11, 1.24), P< 0.0001). An elevation in RDW greater than 19.2% did not result in an additional increased risk of mortality (HR=0.97, 95% CI: 0.91– 1.04, P=0.4617).Conclusion: RDW is an independent predictor of all-cause mortality in DIC patients. Furthermore, there is a nonlinear association between RDW and all-cause mortality of DIC patients.Keywords: red blood cell distribution width, disseminated intravascular coagulation, mortality, MIMIC-III, retrospective study